2013
DOI: 10.1007/s11284-013-1028-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of abundance and co‐occurrence in aquatic plant communities

Abstract: Aquatic plants are well suited as subjects for studies on the distribution and abundance of co-occurring species, especially due to the simple structure of their communities, well defined toposequences and relatively easily measurable environmental factors. Here we show that underwater plants occurring in semi-natural lakes form stable communities, where species interactions dominate over dispersal dynamics to form a modular community structure with a high degree of zonation (turnover) and low within-module sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
4
9
0
Order By: Relevance
“…These findings are consistent with those reported by the few authors who have investigated macrophyte co-occurrence models (Boschilia et al, 2008;Logue et al, 2011;Chmara et al, 2013). When Boschilia and colleagues (2008) investigated the C-score at a coarse spatial scale of analysis in several lagoons across the Paraná River floodplain, they found a non-random macrophyte arrangement due to ecological differences.…”
Section: Macrophyte Co-occurrence In Deep Lakessupporting
confidence: 86%
See 2 more Smart Citations
“…These findings are consistent with those reported by the few authors who have investigated macrophyte co-occurrence models (Boschilia et al, 2008;Logue et al, 2011;Chmara et al, 2013). When Boschilia and colleagues (2008) investigated the C-score at a coarse spatial scale of analysis in several lagoons across the Paraná River floodplain, they found a non-random macrophyte arrangement due to ecological differences.…”
Section: Macrophyte Co-occurrence In Deep Lakessupporting
confidence: 86%
“…This aspect has previously investigated exclusively (Shipley and Keddy, 1987), in lacustrine shoreline vegetation (Keddy, 1983), in a heterogeneous set of shallow lakes (Chmara et al, 2013), and in tropical floodplain lagoons (Boschilia et al, 2008). Indeed, the null model analysis we performed showed that deep lake macrophytes interact, as a whole, in a non-random fashion and some explanatory ecological factors drive macrophyte patterns (LR, T, within the lakes; Chla, Cond and sediment parameters between the lakes).…”
Section: Macrophyte Co-occurrence In Deep Lakesmentioning
confidence: 84%
See 1 more Smart Citation
“…The latter factor, as already mentioned, affects the concentration of inorganic carbon forms in water. The other is that species richness, especially in shallow lakes, is subject to stochastic events such as water fluctuation (Rørslett 1991;Szmeja, 1994) and by the dominance of species interactions over their dispersal dynamics (Chmara et al, 2013). Moreover, in submerged plant communities, the β Simpson diversity index is lower than the α-diversity level and is much smaller than the β species richness (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…In lakes with minor signs of human pressure, submerged plants form communities wherein species interactions dominate over dispersal dynamics to form a highly zoned structure (Chmara et al, 2013). This means that the α-diversity level need not refer to the whole lake but, rather, to its bottom sections (i.e., depth zones).…”
Section: Introductionmentioning
confidence: 99%